PENGARUH PENGGUNAAN HANDPHONE SEBAGAI MEDIA PEMBELAJARAN BAHASA ARAB DI SMA MUHAMMADIYAH 2 BOJA - M Zuhairul Anam; Mukhammad Anieg (As-Sulthan Journal of Education, 2025)
This study aims to analyze the effectiveness of using smartphones in learning Arabic at SMA Muhammadiyah 2 Boja, where students are permitted to bring smartphones into the classroom. The research employs a qualitative approach with observation, interviews, and document analysis as data collection techniques. The results indicate that smartphones can enhance students' learning motivation through interactive applications such as Duolingo, Google Translate, and other digital platforms. However, challenges such as distractions and excessive dependency were also identified. The study concludes by emphasizing the need for balanced supervision policies to maximize the benefits of smartphones in learning.